Permeability prediction of heterogeneous carbonate gas condensate reservoirs applying group method of data handling; Marine and Petroleum Geology; Vol. 139 - Kamali M. Z. Masoud Zanganeh; Davoodi Sh. Shadfar; Ghorbani H. Hamzeh; Wood D. А. David; Mohamadian N. Nima; Lajmorak S. Sahar; Rukavishnikov V. S. Valery Sergeevich; Taherizade F. Farzaneh; Band Sh. S. Shahab (2022, 2022)
Title screen